Archives : principles and practices - Millar, Laura, 1959- (New York : Neal-Schuman Publishers, 2010)
"Divided into four easy-to-follow parts, this authoritative handbook from experienced archivist Laura A. Millar addresses the contextual, strategic, operational, and practical issues associated with creating an archival program. Millar covers the critical topics you need to know to improve your professional skills, including: Establishing principles, policies, and procedures; managing day-to-day operations; caring for different types of archival materials; enhancing outreach and public access; ensuring the growth and sustainability of the institution and its services. This new title is essential for anyone involved in collecting, curating, and managing archives because the accessible, jargon-free language provides both novice and experienced professionals with a clear outline of all the fundamental principles and practices in the field"--Publisher's description.
What are archives? -- Archival institutions : creatures of history and culture -- Archival service : a matter of trust -- Protecting archives -- Provenance, original order and respect des fonds -- Appraising and acquiring archives -- Arranging and describing archives -- Making archives available -- The challenge of digital archives.
Includes bibliographical references and index.
Keywords: Archives -- Administration; Archival materials -- Management; Archival materials -- Conservation and restoration; Cataloging of archival materials; Archives; Cataloging; Library Collection Development